Price momentum and trading volume: evidence from the Western- European stock market - Lopes, David Miguel Silvério (2018)
This study aims to incorporate trading volume information, measured by share turnover, into price momentum strategies. Using the monthly constituents of the STOXX Europe Total Market Index, I find that low-volume portfolios obtain higher momentum returns than simple momentum portfolios, but trading volume does not predict the persistence of price momentum. My results are consistent with the slow information diffusion model of Hong and Stein (1999), and I hypothesize that trading volume might be a proxy for the rate of information diffusion across the market. Lastly, I document that price momentum strategies are only profitable in the second half of my time frame, which goes from January 2004 to December 2014.